Curcumin-Based Nanomedicines in the Treatment of Inflammatory and Immunomodulated Diseases: An Evidence-Based Comprehensive Review - Lucas Fornari Laurindo; Gabriel Magno de Carvalho; Bárbara de Oliveira Zanuso; Maria Eduardo Figueira; Rosa Direito; Ricardo de Alvares Goulart; Daiene Santos Buglio; Sandra Maria Barbalho (MDPI AG, 2023)
Curcumin (CUR) is a polyphenol extracted from the rhizome of Curcuma longa that possesses potent anti-inflammatory and antioxidant potential. Despite CUR's numerous beneficial effects on human health, it has limitations, such as poor absorption. Nano-based drug delivery systems have recently been applied to improve CUR's solubility and bioavailability and potentialize its health effects. This review investigated the effects of different CUR-based nanomedicines on inflammatory and immunomodulated diseases. PUBMED, EMBASE, COCHRANE, and GOOGLE SCHOLAR databases were searched, and the Scale for Assessment of Narrative Review Articles (SANRA) was used for quality assessment and PRISMA guidelines. Overall, 66 studies were included comprising atherosclerosis, rheumatoid arthritis (RA), Alzheimer's disease (AD), Parkinson's disease (PD), multiple sclerosis (MS), Huntington's disease (HD), inflammatory bowel diseases (IBD), psoriasis, liver fibrosis, epilepsy, and COVID-19. The available scientific studies show that there are many known nanoformulations with curcumin. They can be found in nanosuspensions, nanoparticles, nanoemulsions, solid lipid particles, nanocapsules, nanospheres, and liposomes. These formulations can improve CUR bioavailability and can effectively be used as adjuvants in several inflammatory and immune-mediated diseases such as atheroma plaque formation, RA, dementia, AD, PD, MS, IBD, psoriasis, epilepsy, COVID-19, and can be used as potent anti-fibrotic adjuvants in fibrotic liver disease.